Analisis pengaruh pendapatan dan pengetahuan terhadap minat calon nasabah berinvestasi emas di Pegadaian Syariah - Juli Dwina Puspita Sari; Sayyidah Azzafira Azzafira (FEBI IAIN Langsa, 2021)
This study was conducted to examine the effect of income and knowledge on the interest of prospective customers to invest in gold in Pegadaian Syariah. The sampling technique in this study was carried out through probability sampling with simple random sampling. 99 customers who had not invested in gold in the Pegadaian Syariah is definded as the respondents. The method used is multiple regression analysis and hypothesis testing using t-statistics to test the coefficients together with a level of significance of 5%. In addition, the classical assumption test was also carried out which included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results showed that the research data were normally distributed and there were no variables that deviated from the classical assumptions, which also means that the available data has met the requirements to use the multiple regression equation model. Partially, the income and knowledge variable have a positive and significant effect (with a significance value of 0.000 <0.05) on the interest of prospective customers to invest in gold in Pegadaian Syaria Located in Langsa. Meanwhile, simultaneously the income and the knowledge variable have a positive and significant effect (with a significance value of 0.000 <0.05) on the interest of prospective customers to invest in gold Pegadaian Syaria Located in Langsa.